Institutional distance : construct of isomorphism relevant to multinational companies - Krajnović, Ana (Array, 2020)
The institutional environment in which multinational companies act is unique and complex. It is unique in the sense that the subsidiaries of multinational companies are facing dual pressures from both the host country and the country of the parent company. Further, the complexity of the environment presumes the need for global integration and the need for the local adaptation. Although some countries are characterized by a more favourable institutional environment for establishing and expanding business, in other countries the institutional environment is a challenge for multinational companies. In this paper, the author will present the current theoretical knowledge and references in already conducted research regarding the institutional distance in the context of multinational companies and their subsidiaries.